The clinical characteristics, presentation, and treatment outcomes of prolactinomas at Groote Schuur Hospital - Abdalla, Mohamed Abdalla Mansour (Division of Endocrinology and Diabetology, 2021)
Background: Prolactin-secreting tumours( prolactinomas) are the commonest type of pituitary tumour, accounting for approximately 30 to 40 %% of all pituitary adenomas. Although there is ample epidemiologic and clinic data from Industrialised countries there remains sparse data from Africa. Specifically, the clinical presentation, and hormonal deficiencies and treatment outcomes in the South Africa have not been described. Methods: A retrospective study of all patients with a diagnosis of prolactinoma attending the Endocrine and Pituitary Clinics at Groote Schuur Hospital over a 12-month period, between March 2019-March 2020. Patients folders were reviewed to retrieve the following information: demographic data, clinical presentation, clinical signs, prolactinoma phenotype, hormonal deficiencies, treatment modalities and clinical outcomes. Results: Over a 12-month period 52 patients were included in this study, females 73% (n=38), mean age of all participants was 46.1 ± 14.6 years. A macroprolactinoma was present in 67.3% (n=35) of patients and 32.7% (n=17) of patients had a microprolactinoma. In the macroprolactinoma group: the common presenting symptoms were headache 88.6% (n=33), altered vision 40% (n=14) and , in females, amenorrhoea 63.6% (n=14) but a cranial nerve palsy 17.1% (n=6) and apoplexy 5.7% (n=2) were uncommon. . In the microprolactinoma group the common presenting symptoms included amenorrhoea 75% (n=12), galactorrhoea 70.6% (n=12), headache 64.7% (n=11). On presentation the majority of patients with a macroadenoma had at least one hormonal abnormality with hypogonadism 73.1% (n=19) being most common, followed by hypothyroidism 53.8% (n=14) and hypoadrenalism 30% (n=8). Over 50% of patients with a giant adenoma had panhypopituitarism with hypogonadism in 100%, hypothyroidism in 77.8% (n=7) and hypoadrenalism in 66.7% (n=6). Hormonal deficiencies in the microadenoma group on presentation included hypogonadism 64.7% (n=11), hypothyroidism 35.3 (n=6) and one patient had hypoadrenalism. All patients received medical treatment, however, in the macroadenoma group 4 patients required surgical debulking of the tumour, 3 patients required a ventriculo-peritoneal (VP) shunt for hydrocephalus and 2 patients required radiation. After a median follow-up of 46.5 months, the median prolactin level decreased from 322.5 ug/l (94.0-4282.0) at presentation to 17.5 ug/l (8.6-82.5) at follow-up. In parallel there was a reduction of 12.2 ±9.7 mm in tumour size after a mean of 59.8 ±53.3 months. There was resolution of hypogonadism in 56.4% (n=22), of hypothyroidism in 2.7% (n=2) and hypoadrenalism only resolved in 1 patient. Conclusions: Most patients with a prolactinoma are symptomatic and have at least one hormone deficiency on presentation. With medical management most patients experienced a reduction in prolactin levels and tumour size. . This was associated with the resolution of hypogonadism in the majority, however, hypothyroidism and hypoadrenalism are unlikely to resolve despite a reduction in tumour size.